Analisis Disain Midpoint Cycloconverter dengan Pengaturan Tegangan - Setiyono (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This article explains the design of an AC to AC converter with different frequencies and voltages depending on the input. Most electrical equipment circulating in society, such as lighting, water pumps, heaters, cooling machines, are powered by an alternating voltage source with a fixed source voltage and frequency. However, this is not the case with certain types of electric motors in several industries that require a voltage source and changing frequency to regulate their rotational speed. A cycloconverter is an AC to AC converter with frequency settings as well as voltage settings on the output side. This cycloconverter is capable of providing an output frequency n times the source frequency () or () where n is the desired frequency. This research was carried out by building a modeling simulation of a Mid Point type single-phase bridge cycloconverter (middle point) using the Matlab Simulink tool. The simulation results show that the cycloconverter output frequency can be adjusted by setting the switch trigger signal on the positive converter and negative converter with the same wave shape or pattern in the positive cycle and in the negative cycle for each nth divider. At low frequencies the THD (Total Harmonic Distortion) value of the cycloconverter midpoint is greater because of the shape factor on the output side.